Characterization of Novel Synthetic Polyphenols: Validation of Antioxidant and Vasculoprotective Activities - María Jesús Pérez de Vega; Silvia Moreno-Fernández; Gloria María Pontes-Quero; María González-Amor; Blanca Vázquez-Lasa; Beatriz Sabater-Muñoz; Ana M. Briones; María R. Aguilar; Marta Miguel; Rosario González-Muñiz (MDPI AG, 2020)
Antioxidant compounds, including polyphenols, have therapeutic effects because of their anti-inflammatory, antihypertensive, antithrombotic and antiproliferative properties. They play important roles in protecting the cardiovascular and neurological systems, by having preventive or protective effects against free radicals produced by either normal or pathological metabolism in such systems. For instance, resveratrol, a well-known potent antioxidant, has a counteracting effect on the excess of reactive oxygen species (ROS) and has a number of therapeutic benefits, like anti-inflammatory, anti-cancer and cardioprotective activities. Based on previous work from our group, and on the most frequent OH substitutions of natural polyphenols, we designed two series of synthetically accessible bis-polyhydroxyphenyl derivatives, separated by amide or urea linkers. These compounds exhibit high antioxidant ability (oxygen radical absorbance capacity (ORAC) assay) and interesting radical scavenging activity (RSA) values (2,2'-azinobis-(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) and α,α-diphenyl-β-picrylhydrazyl (DPPH) tests). Some of the best polyphenols were evaluated in two biological systems, endothelial cells (in vitro) and whole aorta (ex vivo), highly susceptible for the deleterious effects of prooxidants under different inflammatory conditions, showing protection against oxidative stress induced by inflammatory stimuli relevant in cardiovascular diseases, i.e., Angiotensin II and IL-1β. Selected compounds also showed strong in vivo antioxidant properties when evaluated in the model organism Saccharomyces cerevisiae.